2024
DOI: 10.1002/iid3.1185
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin attenuates inflammation in LPS‐induced lung epithelial cells via the Nrf2 signaling pathway

Pengju Lv,
Pengli Han,
Yuanbo Cui
et al.

Abstract: BackgroundPneumonia is the leading cause of death among children under five, and kill almost two million children each year. Quercetin, a flavonoid polyphenolic compound, exerts many beneficial biological activities, including anti‐inflammatory functions. Our study aimed to investigate the possibility of quercetin as a therapeutic agent for pneumonia and its role in the inflammatory response induced by lipopolysaccharide (LPS).MethodsLPS induced human alveolar epithelial cell A549 as a lung inflammation model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Quercetin is a flavonoid polyphenolic compound that has numerous biological effects. It is shown to have anti-inflammatory effects on lung epithelial cells [29] and periodontal fibroblasts [30]. We have shown that our Co-doped MO could detect quercetin at higher accuracy.…”
Section: Discussionmentioning
confidence: 79%
“…Quercetin is a flavonoid polyphenolic compound that has numerous biological effects. It is shown to have anti-inflammatory effects on lung epithelial cells [29] and periodontal fibroblasts [30]. We have shown that our Co-doped MO could detect quercetin at higher accuracy.…”
Section: Discussionmentioning
confidence: 79%